2018
DOI: 10.3389/fmicb.2018.01341
|View full text |Cite
|
Sign up to set email alerts
|

Amastigote Synapse: The Tricks of Trypanosoma cruzi Extracellular Amastigotes

Abstract: To complete its life cycle within the mammalian host, Trypanosoma cruzi, the agent of Chagas’ disease, must enter cells. Trypomastigotes originating from the insect vector (metacyclic) or from infected cells (bloodstream/tissue culture-derived) are the classical infective forms of the parasite and enter mammalian cells in an actin-independent manner. By contrast, amastigotes originating from the premature rupture of infected cells or transformed from swimming trypomastigotes (designated extracellular amastigot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…After transferrin binding, endosomes are delivered to reservosomes [ 67 ]. As amastigotes and epimastigotes are replicative forms, it would be expected that they would have a larger demand for molecules to sustain proliferation [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…After transferrin binding, endosomes are delivered to reservosomes [ 67 ]. As amastigotes and epimastigotes are replicative forms, it would be expected that they would have a larger demand for molecules to sustain proliferation [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…FAK inhibition was associated with ERK1/2 dephosphorylation and F-actin rearrangement, suggesting a crosstalk between this signaling cascade and the MEK/ERK pathway (Onofre et al, 2019). Likewise, the interaction between HeLa cells and EAs induced N-WASPdependent actin polymerization via PI3K/AKT and ERK but not SFK (Src family kinases) (Bonfim- Melo et al, 2018a). In opposition, previous works on cardiomyocytes have shown that Src was required for TCTs internalization (Melo et al, 2014).…”
Section: Ca 2+ -Dependent Lysosome Exocytosismentioning
confidence: 95%
“…Additionally, it has been shown that amastigotes represent 10% of the parasites circulating in the blood of infected animals during the acute phase of infection (Andrews et al, 1987). Extracellular amastigotes (EAs), originated from premature rupture of infected cells or transformed from BSTs, are also infective and can disseminate in the infected hosts (Walker et al, 2014;Bonfim-Melo et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…reservosomes [67]. As amastigotes and epimastigotes are replicative forms, it would be expected that they would have a larger demand for molecules to sustain proliferation [68].…”
Section: Discussionmentioning
confidence: 99%